DEVELOPMENT OF VIDEO MEDIA ON INDONESIAN LEARNING CLASS X AT SMAN I SANGKAPURA - Retno Fatmalasari; Rufii; Harwanto (Jurnal Mantik, 2022)
The purpose of this development is to produce a video media for learning Indonesian subjects for Class X students. The development model used is Dick & Carey. The stages of development research in the Dick & Carey model consist of ten steps, namely: (1) identifying instructional objectives, (2) conducting instructional analysis, (3) analyzing student characteristics and context, (4) formulating specific instructional objectives, (5) developing assessment instruments, (6) developing instructional strategies, (7) developing and selecting appropriate instructional materials, (8) designing and conducting formative evaluations, (9) revising learning, and (10) designing and conducting summative evaluations. The development process involves subject matter experts, learning design experts and learning media experts to provide feedback and suggestions for improvement. The results of this development research are (1) Development of Video Media in Indonesian Language Subjects is developed based on the analysis of the needs of teachers and students through a needs questionnaire provided by the developer, (2) The results of the validation of material experts, media experts, and design experts on Video Media development products In Indonesian Language Subjects with very feasible criteria to be developed, and (3) Based on the results of research on the development of Video Media in Indonesian Language Subjects, it can be concluded that Video Media learning media is used in developing abilities in designing creative, innovative and interesting learning